Interaction of von Willebrand factor with platelets and the vessel wall - Ruggeri, Z. M.; Mendolicchio, G. L. (Hämostaseologie, 2015)
The initiation of thrombus formation at sites of vascular injury to secure haemostasis after tissue trauma requires the interaction of surface-exposed von Willebrand factor (VWF) with its primary platelet receptor, the glycoprotein (GP) Ib-IX-V complex. As an insoluble component of the extracellular matrix (ECM) of endothelial cells, VWF can directly initiate platelet adhesion. Circulating plasma VWF en-hances matrix VWF activity by binding to structures that become exposed to flowing blood, notably collagen type I and III in deeper layers of the vessel along with microfibrillar collagen type VI in the sub endothelium. Moreover, plasma VWF is required to support platelet-to-platelet adhesion – i. e. aggregation – which promotes thrombus growth and consolidation. For these reasons, understanding how plasma VWF interaction with platelet receptors is regulated, particularly any distinctive features of GPIb binding to soluble as opposed to immobilized VWF, is of paramount importance in vascular biology.This brief review will highlight knowledge acquired and key problems that remain to be solved to elucidate fully the role of VWF in normal haemostasis and pathological thrombosis.
Keywords: Von Willebrand factor